Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.